Long term evaluation of the development of children with cerebral palsy receiving support neurodevelopmental - Harasimowicz, Joanna; Harasimowicz, Paweł; Wawryków, Agata; Korabiusz, Katarzyna; Stecko, Monika (Journal of Education, Health and Sport, 2019)
Recent years show a gradual increase in births of children with cerebral palsy. All children affected by this disease entity should be supported neurodevelopmental. The aim of the work is to assess the long-term development of children with cerebral palsy. It is intended, allowed to increase opportunities and leveling development differences neurological rehabilitation of children covered by unifying therapeutic support and education of parents. An important aspect is the assessment of the effects of neurodevelopmental therapy in the context of the intensity and complexity of the treatment and analysis of the development of motor skills of children covered by development assistance.